2019
DOI: 10.7717/peerj.7225
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of interest explains the size of student evaluation of teaching and learning correlations in multisection studies: a meta-analysis

Abstract: We examined the associations between the size of student evaluation of teaching and learning (SET/learning) correlations and presence of several conflicts of interest (COIs) including corporate, administrative, evaluation unit, SET author, and funder interests. Our meta-analyses of SET/learning correlations reported by multisection studies show that researchers with a vested interest in finding large positive SET/learning correlations found, on average, large positive SET/learning correlations. In contrast, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…As Upton Sinclair (1934Sinclair ( / 1940) once wrote, "It is difficult to get a man to understand something, when his salary depends on his not understanding it" (p. 109). The evidence presented by Uttl et al (2019) is persuasive. They found that SET-learning correlations were much larger when at least one author of a study was associated with an SET corporation.…”
Section: Multisection Studies Of Student Evaluations Of Teachingmentioning
confidence: 98%
See 2 more Smart Citations
“…As Upton Sinclair (1934Sinclair ( / 1940) once wrote, "It is difficult to get a man to understand something, when his salary depends on his not understanding it" (p. 109). The evidence presented by Uttl et al (2019) is persuasive. They found that SET-learning correlations were much larger when at least one author of a study was associated with an SET corporation.…”
Section: Multisection Studies Of Student Evaluations Of Teachingmentioning
confidence: 98%
“…As Clayson (2009) reported, the size of SET-learning correlations were strongly correlated with year of publication. When Uttl et al (2019) looked in more detail at this association, they found that the 69 studies published prior to 1981 yielded an average correlation of r ¼ .31, whereas the 28 studies published in or after 1981 had an average correlation of r ¼ .06. This is a substantial difference, and one wonders how such a difference can be explained.…”
Section: Multisection Studies Of Student Evaluations Of Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-experimental studies are more likely to be confounded, particularly if students could choose the mode of delivery that suited them best. We reviewed the effects on learning, rather than student satisfaction, because learning is a key goal of all universities, and student evaluations are poor predictors of educational attainment (Uttl et al, 2017, 2019). Overall, in this review we aimed to determine (a) what are the learning effects of swapping other content for videos and (b) what are the effects of adding videos to existing course materials?…”
mentioning
confidence: 99%
“…However, taking into consideration our results and the results of previous meta-analyses, especially the comprehensive metaanalysis of Uttl et al (2017), the influence of SET on academic achievement seems to be sufficiently limited to make relevant administrative decisions. Although use of SET as a feedback for teachers' use and as a measure of student satisfaction is not problematic (Spooren et al, 2013;Uttl et al, 2017), the use of SET as a measure of teachers' effectiveness for making administrative decisions about teachers' hiring, firing, promotions, and merit pay is controversial (Uttl et al, 2017(Uttl et al, , 2019American Sociological Association, 2019).…”
Section: Discussionmentioning
confidence: 99%